Effect of Feeding Low Protein Diets on the Performance of Broiler During Hot-Humid Season - Rahman, Muhammad Siddiqur; Pramanik, Md. Ahsan Habib; Basak, Biplob; Tarafdar, Sharif Uddin; Biswas, Sanjib Kumar (International Journal of Poultry Science, 2001)
An experiment was conducted with 180 randomly selected 7th day old ISA I 757 chicks at Bangladesh Agricultural University, Mymensingh. Four different treatments were considered containing 23, 21, 19, and 17% crude protein respectively. Body weights varied significantly (P